EFFECT OF CHRONIC ADMINISTRATION OF HEXANE EXTRACT OF BYRSONIMA CRASSIFOLIA SEED ON Β-CELL AND PANCREATIC OXIDATIVE PARAMETERS IN STREPTOZOTOCIN-INDUCED DIABETIC RAT - Perez Gutierrez, Rosa Martha; Mota Flores, Jose Maria (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: In Mexican traditional medicine, the seeds of Byrsonima crassifolia have been used in the treatment of diabetes, rheumatism and for wound healing. The aim was to evaluate the effect of seeds of B. crassifolia on insulin release from the pancreatic beta cells in streptozotocin-induced diabetic rats. Materials and Methods: In the present study, we evaluated the beneficial effect of seeds B. crassifolia streptozotocin-induced type 1 diabetic rats. Insulin level; insulin sensitivity index, insulin content in pancreas, malonaldehyde, nitric oxide contents, oxidative stress parameters were assayed. Serum glucose levels were determined by the glucose oxidase method. To determine the insulin releasing activity, after extract treatment, the pancreas was excised. Pancreatic sections were processed for examination of insulin-releasing activity using an imunocytochemistry kit. Results: Administration of the hexane extract (200 and 400 mg/kg), exhibited a significant reduction in serum glucose. Administration of streptozotocin decreased the number of beta cells with insulin secretory activity in comparison with intact rats; but treatment with the B. crassifolia seed extract increased significantly the activity of the beta cells in comparison with the diabetic control rats. The extract decreased serum glucose in streptozotocin-induced diabetic rats and increased insulin release from the beta cells of the pancreas. Conclusion: These finding suggest that B. crassifolia seed has beneficial effect for diabetes through decreasing blood glucose and lipid levels, increasing insulin sensitivity index and insulin content, up-regulating antioxidant enzyme activity and decreasing lipid peroxidation.